Group 2 innate lymphoid cells and eosinophilic chronic rhinosinusitis. Issue 1 (February 2019) - Tojima, Ichiro; Shimizu, Takeshi
Abstract : Purpose of review: Chronic rhinosinusitis (CRS) is a heterogeneous disease and is recently classified into two phenotypes, eosinophilic CRS (ECRS) and non-ECRS. ECRS is characterized by Th2-biased eosinophilic inflammation, and non-ECRS is characterized by Th1-biased neutrophilic inflammation. Group 2 innate lymphoid cells (ILC2s) rapidly produce large amounts of Th2 cytokines and exert critical roles in Th2-type immune responses. We summarize our current knowledge about the pathogenic roles of ILC2s in ECRS. Recent findings: The prevalence of ILC2s is increased in nasal polyps, and it is positively correlated with the number of infiltrating eosinophils. Epithelium-derived cytokines (IL-33, IL-25, and thymic stromal lymphopoietin), cysteinyl leukotrienes, and prostaglandin D2 stimulate the production of Th2 cytokines from ILC2s, which drives eosinophilic inflammation in nasal mucosa. Regulation of ILC2s would be a novel therapeutic approach for the refractory and/or recurrent cases of ECRS. Summary: Increased ILC2s play a pivotal role in the pathophysiology of ECRS by producing large amounts of Th2 cytokines, which lead to Th2-type eosinophilic inflammation in nasal polyps.